MUTU MIKROBIOLOGIS MINUMAN JAJANAN DI SEKOLAH DASAR WILAYAH BOGOR TENGAH - Dwi Ariyani; Faisal Anwar (Jurnal Gizi dan Pangan, 2006)
The objectives of the study were to improve the microbiological quality of beverages that significantly affected by the type of selling unit and microbiological quality. The study was carried out from March  to  May 2004.  Three major location were selected, namely : SD Panaragan, SD Empang, and SD Papandayan, Bogor Tengah subdistrict. Determination analysis method of Total Plate Count (TPC) was used. The result of the study showed that beverages with a high risk of microbial contamination at SD Panaragan are “es doger”, “es campur”, and  “es kelapa”, most of these beverages contain coconut milk; at SD Empang are es jeruk and es kemasan; and  at SD Papandayan are es doger, es sirsak, es kemasan and, es teh. Microbiological quality of beverages sold by streetvendor were significantly affected by the types of selling unit.